Just Java 2 - Van der Linden, Peter (Sun Microsystems Press, 2002)
Peter van der Linden's best-selling Just Java has helped thousands of experienced programmers get off to a flying start with Java. Now, it's better than ever. Fully updated for Java 2 JDK 1.3, it's the only concise guide to both the core Java language and the fundamentals of Java server-side programming! Just Java, Fifth Edition organizes Java into five areas: the core language; key libraries such as I/O, networking, and collections; server-side Java; client-side Java; and enterprise Java. Peter van der Linden presents a "straight-to-the-point" introduction to Java object-oriented programming; then covers the crucial information developers need to build working code right away. The second half of the book covers key server-side libraries and programming techniques, including sockets, servlets, JSP, XML, Java database access with JDBC, JavaBeans, and security. The accompanying CD-ROM brings together an extraordinary collection of Java developers' resources: an open-source relational database, the Usenet Java Programmers FAQ and Glossary, a complete servlet system and database inquiry program, sample Java games, links to the Web's best Java resources, and all the book's code examples.